Jagat Saksana Ladi: Servant Leadership in the Perspective of Javanese Culture in Surakarta - Aditya, Ivan; Aji, Aditia Permana; Halyandi, Anang Akbar Rizky Putra; Haq, Muhammad Robeeth Fauzal; Putri, Noor Rizky Tiara; Mulyadi, Asal Wahyuni Erlin (Universitas Gadjah Mada, 2026)
Introduction/Main Objectives: This research explores the application of Servant Leadership through a Javanese cultural lens among public sector leaders in Surakarta. Background Problems: The evolving leadership paradigm requires an understanding of how local implementation is and of the concept of Servant Leadership within the hierarchical Javanese context. Novelty: A theoretical gap exists in integrating Western service models with unique Javanese cultural values.